PERAN PENDIDIKAN KARAKTER DALAM MENGHADIRKAN KEDISIPLINAN PESERTA DIDIK - Putri, Nurlidia; Rahmah Fitri, Dwi; Chanifudin (LPPM STAI Muhammadiyah Probolinggo, 2024)
Character education plays an important role in forming a young generation with noble character and quality. By instilling positive values such as honesty, responsibility, respect, discipline, and social care from an early age, it is expected to present future generations who are not only academically intelligent, but also have strong moral integrity. Through a holistic approach involving family, school, and community, character education can create an environment conducive to developing life skills and emotional maturity in students. This effort is expected to overcome challenges such as moral degradation, juvenile delinquency, and lack of sense of social responsibility that often occur among today's young generation.